Role of Neutral Sphingomyelinase-2 (NSM 2) in the Control of T Cell Plasma Membrane Lipid Composition and Cholesterol Homeostasis - Börtlein, Charlene; Schumacher, Fabian; Kleuser, Burkhard; Dölken, Lars; Avota, Elita (Frontiers in Cell and Developmental Biology, 2019)
The activity of neutral sphingomyelinase-2 (NSM2) to catalyze the conversion of sphingomyelin (SM) to ceramide and phosphocholine at the cytosolic leaflet of plasma membrane (PM) is important in T cell receptor (TCR) signaling. We recently identified PKC as a major NSM2 downstream effector which regulates microtubular polarization. It remained, however, unclear to what extent NSM2 activity affected overall composition of plasma membrane lipids and downstream effector lipids in antigen stimulated T cells. Here, we provide a detailed lipidomics analyses on plasma membrane (PM) fractions isolated from TCR stimulated wild type and NSM2 deficient (NSM) Jurkat T cells. This revealed that in addition to that of sphingolipids, NSM2 depletion also affected concentrations of many other lipids. In particular, NSM2 ablation resulted in increase of lyso-phosphatidylcholine (LPC) and lyso-phosphatidylethanolamine (LPE) which both govern PM biophysical properties. Crucially, TCR dependent upregulation of the important T cell signaling lipid diacylglycerol (DAG), which is fundamental for activation of conventional and novel PKCs, was abolished in NSM cells. Moreover, NSM2 activity was found to play an important role in PM cholesterol transport to the endoplasmic reticulum (ER) and production of cholesteryl esters (CE) there. Most importantly, CE accumulation was essential to sustain human T cell proliferation. Accordingly, inhibition of CE generating enzymes, the cholesterol acetyltransferases ACAT1/SOAT1 and ACAT2/SOAT2, impaired TCR driven expansion of both CD4+ and CD8+ T cells. In summary, our study reveals an important role of NSM2 in regulating T cell functions by its multiple effects on PM lipids and cholesterol homeostasis.